Pembelajaran Fisika Interaktif: Pengembangan Website Materi Gerak Parabola untuk Membangun Minat Belajar - Riki Agus Saputra; Thoha Firdaus; Siti Anisatur Rofiqah (Pendidikan Fisika Universitas Nurul Huda, 2022)
The use of technology in the learning process really helps the learning process to be more advanced and updated. Therefore, prospective educators are required to be able to take advantage of existing technology. This study aims to create interactive learning media for the subject of discussion of Parabolic Motion and to build interest in learning of class X SMA/MA students towards interactive website-based physics learning. This research uses the type of Research and Development (R & D) which adapts the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The media is validated by material expert lecturers and media experts based on predetermined indicators. The results of website development show that the learning media created have very valid criteria with material experts getting a score of 89.7%, media experts scoring 90.4%, and learning interest test scores for 34 students of class X IPA SMA Negeri 1 Semendawai Timur 94%. So it can be concluded that the website created is feasible to be used as an interactive Physics learning medium for class X SMA on the subject of Parabolic Motion And can build interest in student learning.